Kaki Manusia Sebagai Objek Estetik Penciptaan Fotografi Seni - Dira Herawati (Rekam: Jurnal Fotografi, Televisi, Animasi)
Accountability report is a written description of creative experiences as an artist or a photographer of aesthetic exploration efforts on the image and the idea of a human as a basic stimulant for the creation of works of art photography. Human foot as an aesthetic object is a problem that relates to various phenomena that occur in the social sphere, culture and politics in Indonesia today. Based on these linkages, human feet would be formulated as an image that has a value, and the impression of eating alone in the creation of a work of art photography. Hence the creation of this art photography entitled The Human Foots as Aesthetic Object  Creation of Art Photography. Starting from this background, then the legs as an option object art photography, will be managed creatively and systematically through a phases of creation. The creation phases consist of: (1) the exploration of discourse, (2) artistic exploration, (3) the stage of elaboration photographic, (4) the synthesis phase, and (5) the stage of completion. Methodically, through the phases of the creative process  through which this can then be formulated in various forms of artistic image of a human foot. The various forms of artistic images generated from the foots of its creation process, can be summed up as an object of aesthetic order 160 Kaki Manusia Sebagai Objek Estetik Penciptaan Fotografi Seni in the photographic works of art. It is specifically characterized by the formation of ‘imaging the other’ behind the image seen with legs visible, as well as of the various forms of ‘new image’ as a result of an artistic exploration of the common image of legs visible. In general, the whole image of the foot in a photographic work of art has a reflective relationship with the social situation, cultures, and politics that developed in Indonesian society, by value, meaning and impression that it contains.Keywords: human foots, aestheti,; social phenomena, art photography, images